Photoactivatable RNAi for cancer gene therapy triggered by near-infrared-irradiated single-walled carbon nanotubes - Ren XL (Dove Medical Press, 2017)
Xueling Ren, Jing Lin, Xuefang Wang, Xiao Liu, Erjuan Meng, Rui Zhang, Yanxiao Sang, Zhenzhong Zhang Key Laboratory of Targeting Therapy and Diagnosis for Critical Diseases, School of Pharmaceutical Sciences, Zhengzhou University, Zhengzhou, People’s Republic of China Abstract: The efficacy of RNA interference (RNAi)-based cancer gene therapy is limited by its unexpected side effects, thus necessitating a strategy to precisely trigger conditional gene knockdown. In this study, we engineered a novel photoactivatable RNAi system, named as polyetherimide-modified single-wall carbon nanotube (PEI-SWNT)/pHSP-shT, that enables optogenetic control of targeted gene suppression in tumor cells. PEI-SWNT/pHSP-shT comprises a stimulus-responsive nanocarrier (PEI-SWNT), and an Hsp70B'-promoter-driven RNAi vector (pHSP-shT). In response to near-infrared (NIR) light irradiation, heating of PEI-SWNT in breast MCF-7 cells triggered gene knockdown targeting human telomerase reverse transcriptase through RNAi, with the gene-knockdown activity capable of being switched off by extinguishing the NIR. Furthermore, we demonstrated that the photoactivatable RNAi system exhibited higher antitumor activity by combining gene therapy and photothermal therapy, both in vitro and in vivo. Optogenetic control of RNAi based on an NIR-activated nanocarrier will potentially facilitate improved understanding of molecular-targeted gene therapy in human malignant tumors. Keywords: near-infrared light response, SWNT, RNAi, Hsp70B' promoter